ANALYSIS OF GENETIC PARAMETERS FOR BEAN PHYSICAL QUALITY CHARACTERS AND CLUSTERIZATIONS OF ELEVEN GENOTYPES OF ROBUSTA COFFEE (Coffea canephora) - Rubiyo Rubiyo; Edi Wardiana (Indonesian Journal of Agricultural Science, 2013)
The genetic parameters of coffee related to their bean physical quality characters are important for breeder to improve the  bean quality. Eleven genotypes of robusta coffee were identified and their genetic relationship to the bean physical quality were characterized. The research was conducted at coffee plantation of the Association of Indonesian Coffee Exporters in West Lampung, altitude of 800 m above sea level, Latosol type of soil, and A type of climate, starting from 2010 to 2012. The objectives of this study were to estimate the genotypic coefficient of variation, heritability and genetic advance of the bean physical quality characters, and clusterization analysis of eleven genotypes of robusta coffee. A randomized complete block design with eleven treatments of coffee genotypes and three replications was used in this study. The results showed that the estimated values of genotypic coefficient of variation, heritability and genetic advance for small-size normal bean characters of robusta coffee were very high, so the genetic improvement for these characters has a high probability of success by direct selection. Clusterization of the genotypes resulted three clusters with their respective characteristics. The study implies that future breeding program especially for hybridization should be conducted between genotypes arising from different clusters to obtain the possible high heterosis effects.